THE INFLUENCE OF SCARCITY TOWARDS PEOPLE’S WILLINGNESS TO PAY PREMIUM PRICES FOR LUXURY FASHION - Cherry Josephine; Charly Hongdiyanto (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2026)
The growth of the luxury fashion industry in Indonesia, particularly in the aspirational luxury segment, highlights the importance of understanding psychological factors influencing purchase intention. This study examines the effect of perceived scarcity on purchase intention, with perceived quality, perceived uniqueness, and perceived value as mediating variables. A quantitative survey was conducted with 210 female respondents aged 20 years and above in Java Island who showed interest in aspirational luxury fashion brands. Purposive sampling was applied, and the data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The findings reveal that perceived scarcity significantly influences perceived quality and purchase intention, but not perceived uniqueness or perceived value. Perceived quality and perceived uniqueness positively affect perceived value, which in turn significantly influences purchase intention. These results indicate that value creation and symbolic differentiation play a more important role in driving purchase intention than product scarcity alone in the aspirational luxury fashion context.